Cellular immunity against cytomegalovirus and risk of infection after kidney transplantation - Blom, Kjersti B.; Kro, Grete B.; Midtvedt, Karsten; Jenssen, Trond G.; Reisæter, Anna Varberg; Rollag, Hallvor; Hartmann, Anders; Sagedal, Solbjørg; Sjaastad, Ivar; Tylden, Garth; Njølstad, Gro; Nilsen, Einar; et al. (Frontiers in Immunology, 2024)
Cytomegalovirus (CMV) infection remains a challenge following kidney transplantation (KTx). Currently, CMV-IgG serostatus at transplantation is used to individualize CMV preventive strategies. We assessed the clinical utility of CMV-IGRA for predicting CMV infection following KTx. We performed a nationwide prospective cohort study from August 2016 until December 2022. Data from all adult KTx recipients in Norway, n=1,546 (R+; n=1,157, D+/R-; n=260, D-/R-; 129), were included with a total of 3,556 CMV-IGRA analyses (1,375 at KTx, 1,188 at eight weeks, 993 one-year after KTx) and 35,782 CMV DNAemia analyses. In R+ recipients CMV-IGRA status, measured at any of the time-points, could not identify any differential risk of later CMV infection. D+/R- recipients remaining CMV-IGRA negative 1-year after transplantation (regardless of positive CMV DNAemia and/or CMV IgG status at that time) had increased risk of developing later CMV infection compared to D+/R- recipients who had become CMV-IGRA positive (14% vs. 2%, p=0.01). Knowledge of pre-transplant CMV-IGRA status did not provide additional information to CMV-IgG serostatus that could improve current post-transplant CMV treatment algorithms. However, D+/R- recipients with a persisting negative CMV-IGRA one-year after transplantation remained at increased risk of experiencing later CMV infection. Therefore we advocate post-transplant CMV-IGRA monitoring in these patients.